Initial observations on age, gender, BMI and hypertension in antibody responses to SARS-CoV-2 BNT162b2 vaccine. (June 2021) - Pellini, Raul; Venuti, Aldo; Pimpinelli, Fulvia; Abril, Elva; Blandino, Giovanni; Campo, Flaminia; Conti, Laura; De Virgilio, Armando; De Marco, Federico; Di Domenico, Enea Gino; Di Bella, Ornella; Di Martino, Simona; et al.
Abstract: Background: Literature data suggests that age, gender and body mass index (BMI) could be associated with difference in immune responses to vaccines. The first goal of the study was to analyze the antibody titre seven days after the second dose of BNT162b2 vaccine in a group of 248 healthcare workers (HCWs). The second goal was to analyze how antibody titre changes in correlation with age, gender, BMI and hypertension. Methods: An immunogenicity evaluation was carried out among HCWs vaccinated at the Istituti Fisioterapici Ospitalieri (IFO), Rome, Italy. All HCWs were asked to be vaccinated by the Italian national vaccine campaign at the beginning of 2021. 260 vaccinated HCWs were enrolled in the study. All eligible participants were assigned to receive the priming dose in two weeks' time and the booster dose exactly 21 days thereafter. Blood and nasopharyngeal swabs were collected at baseline and 7 days after second dose of vaccine. Quantitative measurements of IgG antibodies against S1/S2 antigens of SARS-CoV-2 were performed with a commercial chemiluminescent immunoassay. Presence of SARS-Cov-2 in nasopharyngeal swab was determined by commercial RT-PCR testing. Findings: 248 HWCs were analyzed, 158 women (63.7%) and 90 men (36.3%). After the second dose of BNT162b2 vaccine, 99.5% of participants developed a humoral immune response. The geometric mean concentration of antibodies among the vaccinated subjects after booster dose (285.9 AU/mL 95% CI: 249.5–327.7) was higher than that of human convalescent sera (39.4 AU/mL, 95% CI: 33.1–46.9), with p <0.0001. Multivariate linear regression analysis of AU/mL by age, gender and BMI multivariate was performed by the inclusion of covariates. This analysis demonstrated that age ( p <0.0001) and gender ( p = 0.038) are statistically associated with differences in antibody response after vaccination, whereas BMI and hypertension have no statistically significant association ( p = 0.078 and p = 0.52 respectively). Interpretation: 99.5% of HCW developed a humoral immune response and female and young participants seem to have an increased capacity to mount humoral immune responses. BMI and hypertension seem not associated with difference in immune response to the vaccine. Funding: None.